2020
DOI: 10.30605/jsgp.3.2.2020.262
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Speaking Assessment Types in Textbook “When English Rings a Bell Grade VII”

Abstract: Speaking can be said as one of the four basic skills in English. In every English textbook, there must be a speaking assessment. This research aims to analyze the five types of speaking assessments in the textbook “When English Rings a Bell for Grade VII”. The textbook analysis in this study considered five types in speaking assessment there are: 1. Imitative speaking tasks, 2. Intensive speaking tasks, 3. Responsive speaking tasks, 4. Interactive speaking tasks and, 5. Extensive speaking tasks. This study inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…[14] found that the topic of the material in textbook, organization, cohesion and cohesive, vocabulary, and grammatical features needed to be improved. [15] elaborated that the material found in the text book is skills-based like listening, speaking, reading, and writing. [16] added that learning materials in the textbook are discourse in the form of dialogs, stories, chants, and reading texts.…”
Section: Introductionmentioning
confidence: 99%
“…[14] found that the topic of the material in textbook, organization, cohesion and cohesive, vocabulary, and grammatical features needed to be improved. [15] elaborated that the material found in the text book is skills-based like listening, speaking, reading, and writing. [16] added that learning materials in the textbook are discourse in the form of dialogs, stories, chants, and reading texts.…”
Section: Introductionmentioning
confidence: 99%